Advances in Knowledge Management Celebrating Twenty Years of Research and Practice - Bolisani, Ettore; Handzic, Meliha; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book celebrates the past, present and future of knowledge management. It brings a timely review of two decades of the accumulated history of knowledge management. By tracking its origin and conceptual development, this review contributes to the improved understanding of the field and helps to assess the unresolved questions and open issues. For practitioners, the book provides a clear evidence of value of knowledge management. Lessons learnt from implementations in business, government and civil sectors help to appreciate the field and gain useful reference points. The book also provides guidance for future research by drawing together authoritative views from people currently facing and engaging with the challenge of knowledge management, who signal a bright future for the field.
Analyzing the Past: Knowledge Management: Origins, History and Development -- Knowledge Management Concepts and Models -- A Descriptive Analysis of Knowledge Management Research: Period from 1997 to 2012 -- Acting in Present: Knowledge Management in the Public Sector: UK Case Study Perspectives -- Supporting Business Managers with Knowledge Management -- Understanding and Improving the Professional Toolbox: Communities of Practice as a Paradigmatic Lesson for Knowledge Management -- Predicting the Future: Future Research About Knowledge and Knowledge Management - Results from the Global Knowledge Research Network Study -- What Practitioners (Should) Want and Expect: A Personal Perspective -- The Next Generation of Knowledge Management: Mapping-based Assessment Models.
Keywords: Economics; Data mining; Business planning; Management information systems; Economics/Management Science; Business Information Systems; Data Mining and Knowledge Discovery; Organization/Planning.